2018
DOI: 10.12669/pjms.344.14602
|View full text |Cite
|
Sign up to set email alerts
|

Association between grades of Hydronephrosis & detection of urinary stones by ultrasound imaging

Abstract: Objective:To correlate between hydronephrosis grades and detection of urinary stones by B-mode ultrasound imaging.Methods:This study included 210 ultrasound reports of patients who underwent abdominal ultrasound imaging in the period from 1st January 2016 to 31st October 2017, and diagnosed as hydronephrosis. Data collected from the ultrasound reports. The detection rates of stones using B-mode ultrasound imaging compared in different grades of hydronephrosis. Chi-square test and Odds Ratio (OR) were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…This is consistent with another previous study by Alshoabi, who reported that calculi were the cause of HN in 60% of cases. 11 This study showed predilection of HN to male gender. This predilection was explained by the results of a previous study by Ahmed et al who reported that urinary tract calculi, which are the most common cause of HN, are formed more common in males due to hormonal effects.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This is consistent with another previous study by Alshoabi, who reported that calculi were the cause of HN in 60% of cases. 11 This study showed predilection of HN to male gender. This predilection was explained by the results of a previous study by Ahmed et al who reported that urinary tract calculi, which are the most common cause of HN, are formed more common in males due to hormonal effects.…”
Section: Discussionmentioning
confidence: 58%
“…This is consistent with another previous study by Alshoabi, who reported that calculi were the cause of HN in 60% of cases. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Failure of the urine excretion process is caused by an obstructive or nonobstructive process due to a functional or structural change of the urinary system. 1 The presentation of hydronephrosis can be unilateral or bilateral, physiologic or pathologic, and acute or chronic. 6 Each year, approximately 42,000 new cases of hydronephrosis are diagnosed with a two-to-one male-tofemale prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Hydronephrosis is graded on a scale from 0 to 4, 4 being the most severe, indicating increased renal cortex damage and decreased renal function. 1,7 The severity of hydronephrosis can be determined by evaluating the kidneys' sonographic features on a renal sonogram. Grade 0 is an absence of hydronephrosis in the collecting system and is visualized as normal-appearing kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…7 The literature reported resistive index sensitivity and specificity, 75.5% and specificity 92.5% respectively. 8 Literature shows that the resistive index is influenced by many other factors such as the age of patient, level of renin in plasma, and the simultaneous presence of diabetes mellitus, hypertension, cardiac diseases, and variety of kidney disorders. The presence of any of these factors may rise the values of resistivity index even in there is no renal obstruction.…”
Section: Introductionmentioning
confidence: 99%